The Considerations and Controversies in Using High-Flow Nasal Oxygen with Self-Prone Positioning in SARS-CoV-2 COVID-19 Disease. (24th May 2021) - Nunn, Kieran P.; Blackstock, Murray J.; Ellis, Ryan; Sheikh, Gauhar; Morgan, Alastair; Rhodes, Jonathan K. J.
Abstract : Evidence exists for the use of high-flow nasal oxygen (HFNO) in the general critical care population for acute hypoxemic respiratory failure. There is discord between guidelines for hypoxemia management in COVID-19. Both noninvasive management and intubation present risk to patients and staff and potentially overwhelm hospital mechanical ventilator capacity. The use of HFNO has been particularly controversial in the UK, with oxygen infrastructure failure. We discuss our experience of managing COVID-19 with HFNO and awake self-prone positioning. We focus upon the less-usual case of an eighteen-year-old female to illustrate the type of patient where HFNO may be used when perhaps earlier intubation once was. It is important to consider the wider implications of intubation. We have used HFNO as a bridge to intubation or as definitive management. As we await clinical trial evidence, HFNO with self-prone positioning has a role in COVID-19 for certain patients. Response parameters must be set and reviewed, oxygen infrastructure considered, and potential staff droplet exposure minimised.